Determinan Kredit Usaha Mikro, Kecil dan Menengah (UMKM) di Indonesia - Afifah, Aisyah Nur; Setyaningtyas, Ashita; Sari, Fahra Permata; Kartiasih, Fitri (KINERJA, 2024)
Micro, Small, Medium Enterprises (MSMEs) are productive businesses owned by individuals and/or entities that meet the MSME criteria as stipulated in the law. The purposes of this study are (1) to find out the general description of the development of MSME credit in Indonesia in 2016-2018, (2) to analyze the effect of NPL credit (Non-Performing Loan), the proportion of internet users, investation (PMTB), life expectancy, average length of schooling, and economic growth of MSME loans in Indonesia in 2016-2018. The data in this study took secondary data for the period 2016 to 2018. The data were analyzed using Panel Data Regression. The results showed that NPL credit, the proportion of internet users, PMTB, and life expectancy had a significant positive effect on the number of MSME loans in Indonesia.